2013
DOI: 10.3109/07420528.2013.829846
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype-related differences in childhood and adolescent aggression and antisocial behavior – A review of the literature

Abstract: Eveningness has been found to negatively affect adolescents' sleep and daytime functioning. Furthermore, eveningness is associated with greater impulsivity than morningness. Externalizing behavior could be chronotype-related, implying that the alteration of the circadian rhythm itself is connected to aspects of emotion and emotion regulation. The present study investigated chronotype-related differences in emotional and behavioral problems, especially aggression and antisocial behavior in children and adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 78 publications
5
62
0
1
Order By: Relevance
“…BISS induced by this mismatch might mediate the relationship between eveningness and academic performance. Similarly, the relationships between eveningness and impulsivity, inattention, or depression reported in previous studies 6,31,32 may partly be moderated by BISS.…”
Section: Discussionmentioning
confidence: 91%
“…BISS induced by this mismatch might mediate the relationship between eveningness and academic performance. Similarly, the relationships between eveningness and impulsivity, inattention, or depression reported in previous studies 6,31,32 may partly be moderated by BISS.…”
Section: Discussionmentioning
confidence: 91%
“…Secondly, while our protocol controlled for the effect of age and gender, no data were obtained regarding pubertal stage, although some sleep changes during adolescence are closely correlated to pubertal maturation (Carskadon, 1990). Future studies should also control for circadian preference which plays a role in emotional problems aggressive behaviors and sleep/ wake patterns (Dagys et al, 2011;Gelbmann et al, 2012;Hsu et al, 2012;Lange & Randler, 2011;Schlarb et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Biases in temporal framing have far reaching consequences for cognitive processes (Zajenkowski et al 2015), affective states (Matthews and Stolarski 2015), values and behavior in many areas (see Stolarski et al 2015a). More specifically, recent research revealed measures of TP dimensions predict variables that have been linked to aggression, including negative mood (Stolarski et al 2014;Apter et al 1990), impulsive behavior (MacKillop et al 2006;Manuck et al 1998), relationship satisfaction (Stolarski et al 2015b;Bookwala et al 1994), substance use and abuse (Keough et al 1999;Brady et al 1998), chronotype Schlarb et al 2014) and affective disorders (Gruber et al 2012;Van Praag 1986). The links between TP and behaviors which have been independently associated with aggression gives rise to a question: to what degree are the various TPs related to aggressive emotions and aggressive behavior?…”
Section: Introductionmentioning
confidence: 97%